Astrocyte disruption of neurovascular communication is linked to cortical damage in an animal model of multiple sclerosis. Issue 5 (9th February 2018) - Eilam, Raya; Segal, Menahem; Malach, Rafael; Sela, Michael; Arnon, Ruth; Aharoni, Rina
Abstract: To elucidate mechanisms contributing to cortical pathology in multiple sclerosis (MS), we investigated neurovascular aberrations, in particular the association of astrocytes with cortical neurons and blood vessels, in mice induced with experimental autoimmune encephalomyelitis (EAE). Blood–brain barrier (BBB) dysfunction was evident by leakage of the tracer sodium fluorescein, along with reduced expression of claudin‐5 by endothelial cells and desmin by pericytes. Immunohistological and ultrastructural analyses revealed detachment of the astroglial cell bodies from the blood vessels and loss of their connections with both the blood vessels and the neuronal synapses. Furthermore, examination of individual astrocytic processes at cortical layer IV, where well‐defined neuronal columns (barrels) are linked to functional properties, revealed loss of astrocytic confinement to the functional neuronal boundaries. Thus, in contrast to the highly modulated patches of astrocyte processes in naïve mice overlapping the barrel cores, in EAE‐mice process distribution was uniform ignoring the barrel boundaries. These aberrations are attributed to the surrounding inflammation, indicated by T‐cells presence in the cortex as well as in the subcortical white matter and the meninges. Immunomodulatory treatment with glatiramer acetate partially abrogated the neurovascular damage. These combined findings indicate that under inflammatory conditions, activated perivascular astrocytes fail in neuro‐hemodynamic coupling, resulting in obstructed cross‐talk between the blood vessels and the neurons. We propose that loss of cortical astrocytic regulation and fine‐tuning between the blood supply and the neuronal needs contributes to the neurological impairment and cognitive decline occurring in EAE/MS as well as to the disease progression. Main Points: During inflammation, astrocytes detach from the blood vessels and lose their confinement to the functional neuronal boundaries. Disrupted neurovascular communication contributes to cortical damage and neurological impairment in EAE/MS.